PENGARUH KONFLIK KELUARGA-PEKERJAAN TERHADAP KINERJA PEGAWAI WANITA PADA INSTANSI STKIP-PGRI PONTIANAK - B31109054, EMA PURWANTY (Jurnal Manajemen Update, 2013)
The purpose of this study was to determine the effect of family - work conflict to job performance on women employees in STKIP-PGRI Pontianak. This research used the design causality. This research used the causal method. The samples of this research are 45 married women, using census sample method. The data were collected with a questionnaire and a quantitative analysis of multiple linear regression. The result of the research shows that: (1) Partially, there is two variable significantly affect the performance which is variable pressure of marriage and variable parental involment of lack. (2) Simultaneously, there arent significant influence between parenting stress, marital stress, lack of involvement as a wife, a lack of parental involvement, and intervention on job performance. The implication of this research is the conflict that arise in the family can affect a persons job in partially. That is, a worker who bring the family issues of home will affect job performance. Keywords: Family-work conflict, job performance on employees